2015
DOI: 10.1002/ece3.1446
|View full text |Cite
|
Sign up to set email alerts
|

An optimal proportion of mixing broad‐leaved forest for enhancing the effective productivity of moso bamboo

Abstract: Moso bamboos (Phyllostachys edulis) are important forestry plants in southern China, with substantial roles to play in regional economic and ecological systems. Mixing broad-leaved forests and moso bamboos is a common management practice in China, and it is fundamental to elucidate the interactions between broad-leaved trees and moso bamboos for ensuring the sustainable provision of ecosystem services. We examine how the proportion of broad-leaved forest in a mixed managed zone, topology, and soil profile affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Moso bamboo sequesters 4.91–5.45 t C ha −1 each year ( Zhou & Jiang, 2004 ), showing great potential for alleviating global warming by carbon fixation. Previous studies on Moso bamboo have concentrated on carbon storage, balance and its distribution in the ecosystem ( Li et al, 2013 ), productivity of bamboo forest ( Cheng et al, 2015 ; Isagi et al, 1997 ), and the variation in soil organic carbon stocks ( Guan et al, 2015 ). Previous studies reported a close relationship between R s and biotic factors in other forest types ( Hibbard et al, 2005 ), suggesting a coupling between forest canopy assimilation and carbon emissions from soil.…”
Section: Introductionmentioning
confidence: 99%
“…Moso bamboo sequesters 4.91–5.45 t C ha −1 each year ( Zhou & Jiang, 2004 ), showing great potential for alleviating global warming by carbon fixation. Previous studies on Moso bamboo have concentrated on carbon storage, balance and its distribution in the ecosystem ( Li et al, 2013 ), productivity of bamboo forest ( Cheng et al, 2015 ; Isagi et al, 1997 ), and the variation in soil organic carbon stocks ( Guan et al, 2015 ). Previous studies reported a close relationship between R s and biotic factors in other forest types ( Hibbard et al, 2005 ), suggesting a coupling between forest canopy assimilation and carbon emissions from soil.…”
Section: Introductionmentioning
confidence: 99%
“…Many biological measures exhibit skewed rather than normal distributions yet their distributions fit TPL. An example is the diameter at breast height of moso bamboos (Cheng et al 2015), which is skewed yet conforms to TPL. The deviation of plant biomass from a normal distribution is likely related to the spatial distribution of soil nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…However, mixed P. edulis forests can effectively compensate for this weakness. Additionally, mixed forest construction improves forestland productivity while lowering the incidence and severity of insect pest and microbial pathogen attacks [8][9][10]. Mixing of C. illinoinensis with many other species has also showed a good growth trend [11,12].…”
Section: Introductionmentioning
confidence: 99%